Aftermarket short covering in ipos and long-term stock liquidity - Tolentino, Rodrigo Andrade (2009)
This study investigates the effect of the aftermarket short covering (ASC) carried out by the underwriter during the price stabilization period on stock long-term liquidity. Because the ASC increases liquidity during the stabilization period and liquidity is a persistent characteristic of stocks, the ASC can increase long-term liquidity. In fact, we show that the ASC has a positive effect on liquidity over the 6 months subsequent to the stabilization period. This positive relation holds true even after controlling for many variables found important to explain liquidity by previous authors and the instrumentalization of the ASC.